Strategic Water Iraq and Security Planning in the Euphrates-Tigris Basin - Lorenz, Frederick (Marine Corps University Press (MCUP), 2013)
After the final phase of drawdown of U.S. troops in Iraq, it is important to do what we can to help maintain a level of stability and to look ahead to emerging security threats. Strategic Water: Iraq and Security Planning in the Euphrates-Tigris Basin by Frederick Lorenz and Edward J. Erickson makes an important contribution to this effort by taking a close look at a serious problem that is often neglected-the decline in freshwater availability and its impact on regional security